Parents' willingness to vaccinate their daughters with human papillomavirus vaccine and associated factors in Debretabor town, Northwest Ethiopia: A community-based cross-sectional study - Getie Mihret Aragaw; Tazeb Alemu Anteneh; Saron Abeje Abiy; Mulunesh Abuhay Bewota; Getie Lake Aynalem (Taylor & Francis Group, 2023)
The Human Papilloma Virus (HPV) is the primary causative agent of cervical cancer. Vaccination against the HPV infection is an effective prevention measure for HPV-related diseases. This study aimed to assess parents' willingness to vaccinate their daughters with Human Papillomavirus vaccine and associated factors in Debre Tabor town. A community-based cross-sectional study was conducted among parents of daughters in Debre Tabor town, and a cluster sampling technique was used to select 738 study participants. A structured and interviewer-administered questionnaire was used to collect the data. Data were entered into EPI data version 4.6 and exported to SPSS version 26 for analysis. Multivariable logistic regression was done and a p-value of ≤ 0.05 was used to declare the level of significance. In this study, parents' willingness for HPV vaccination was found to be 79.10% (95% CI: 76.00, 82.00). Parents having media exposure, had good knowledge of HPV infection, and HPV vaccine, positive attitude, and positive perceived behavioral control toward the HPV vaccine had statistically significant association with willingness for the HPV vaccination of their daughters. Parents' willingness to HPV vaccination for their daughters was higher compared with a previous study done in the setting. Parental knowledge and their beliefs on HPV vaccination, and media exposure play an important role in the HPV vaccination of adolescents. Strengthening community-based education and effective promotion through multimedia on HPV infection and its prevention, addressing parental safety concerns and promoting their positive beliefs about the vaccine are important to increase parents' willingness.